Meaning-Symbol relations ant the Theology of punishment: Birth of rituals of Torture - seyyed mohammad javad sadati (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2021)
AbstractTechnical studies of criminal law rarely discuss the social aspects of punishment. Punishment has a deep relation with other social institutions such as power, culture and punishment is part of the social structure. As a result, this phenomenon has close relation with other parts of social structure. Torture, as one shape of penal reaction, is no exception to this pervasive rule. Birth and continuation of these ritual punishments have complex and deep relations with other social phenomena. However, technical studies of criminal law are reluctant to examine the hidden sociological aspects of torture.  The Sociology of punishment tries to show thesehidden relations. Sociological study shows that torture has a deep relation with the identity of the collective conscious. In this research, with the sociological method, I try to analyze the process of birth and continuation of rituals of torture in ancient Iran.Keywords: Collective unconscious, Meaning-Symbol relations, Ritual life, Rituals of torture, Theology of punishment